Sandplay wisdom : understanding sandplay therapy - Mitchell, Rie Rogers, 1940-; Friedman, Harriet S., 1930- (Milton Park, Abingdon, Oxon ; New York, NY : Routledge, 2021)
"Sandplay Wisdom provides key concepts for understanding and using sandplay therapy effectively, distilling insight from more than four decades of experience. Rie Rogers Mitchell and Harriet S. Friedman provide both core principles and hard-won practical tips to deepen understanding of sandplay therapy for both experienced and novice practitioners. The principles presented provide key insight into many important therapeutic dimensions, including childhood trauma, archetypal life stages, age and gender issues, transference and countertransference, as well as sandplay with both adults and children. The book is illustrated with case material and images from real sessions throughout and provides invaluable guidance on working with clients in a vast range of contexts. This important book will be essential reading for all sandplay therapists in practice and in training. It will also be of great interest practitioners, academics and scholars of play and arts therapies"--
OCLC-licensed vendor bibliographic record.
Keywords: Sandplay -- Therapeutic use; PSYCHOLOGY / Mental Health; PSYCHOLOGY / Movements / Jungian